Çevresel Tarih Açısından Bataklık Kurutma ve Göl Islahı: Bilecik Gölpazarı Örneği - Kübra Çaylı (Coğrafi Bilimler Dergisi)
Marshes, with their rich biodiversity, are crucial to ecosystems but have been transformed over time for economic reasons. In the Ottoman Empire, reclamation works were carried out across vast areas, including Rumelia, Anatolia, and the Arab world. One such area is Gölpazarı, currently in Bilecik Province. In the 19th century, Gölpazarı, previously part of Bursa Province, was valued for its fertile land and strategic location, but its marshes hindered agriculture and settlement. The reclamation efforts to drain these marshes ignored the region's geographical and climatic characteristics, leading to environmental problems instead of economic gains. This study examines the environmental impacts of these reclamation efforts using Ottoman and Republican-era archival sources, along with other scientific studies, and The current reflections of the environmental and economic effects of the reclamation activities in Gölpazarı were also emphasized.